Beacon Virtua: A Virtual Reality Simulation Detailing the Recent and Shipwreck History of Beacon Island, Western Australia - Woods, Andrew; Oliver, Nick; Bourke, Paul; Green, Jeremy; Paterson, Alistair (Springer, 2019)
Beacon Virtua is a project to document and virtually preserve a historically significant offshore island as a virtual reality experience. In 1629, survivors of the wreck of VOC ship Batavia took refuge on Beacon Island, Western Australia, followed by a mutiny and massacre. In the 1950s the island became the base of a successful fishing industry, and in 1963 human remains from Batavia were located. The fishing community has recently been moved off the island to protect and preserve the site and allow a thorough archaeological investigation of the island. Beacon Virtua exposes users to the history of both the shipwreck survivors and the fishing community. The project uses the virtual environment development software Unity to present a simulation of the island, with 3D models of buildings and jetties, photogrammetric 3D reconstructions of graves and other features, 360° photographic panoramas, and information on the history of the island. The experience has been made available on a wide range of different platforms including via a web-page, as part of an exhibition, and on head mounted displays (VR headsets). This chapter discusses the features included in Beacon Virtua, the storytelling techniques used in the simulation, the challenges encountered and solutions used during the project.